2011
DOI: 10.4081/gh.2011.179
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the positional difference between two common geocoding methods

Abstract: Abstract. Geocoding, the process of matching addresses to geographic coordinates, is a necessary first step when using geographical information systems (GIS) technology. However, different geocoding methodologies can result in different geographic coordinates. The objective of this study was to compare the positional (i.e. longitude/latitude) difference between two common geocoding methods, i.e. ArcGIS (Environmental System Research Institute, Redlands, CA, USA) and Batchgeo (freely available online at http://… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 26 publications
1
50
0
3
Order By: Relevance
“…Estos porcentajes se aproximan a los obtenidos en un estudio 14 en el que un software GIS geocodificó el 97% de las direcciones. En otro trabajo este porcentaje con el programaArcGis fue de 94% 13 .…”
Section: Discussionunclassified
“…Estos porcentajes se aproximan a los obtenidos en un estudio 14 en el que un software GIS geocodificó el 97% de las direcciones. En otro trabajo este porcentaje con el programaArcGis fue de 94% 13 .…”
Section: Discussionunclassified
“…There have been a number of studies that have assessed geocoding techniques, positional accuracy (Zandbergen 2008;Ward et al 2005;Duncan et al 2011) and the impacts of geocoded or matched outlet proportion and positional accuracy upon resulting analyses (Krieger et al 2001;Ratcliffe 2004;Zandbergen 2007). In particular, Zandbergen (2007) has shown that wherever possible, high resolution address data (building-level) should be employed as the reference dataset particularly when finescale analysis is being performed.…”
Section: Methods Geocoding Licence Datamentioning
confidence: 99%
“…We thank Mak for his positive comments about our article previously published in Geospatial Health (Duncan et al, 2011), and for bringing attention to the important issue of potentially compromising patient privacy (including protected health information) when geocoding such data using online services. We acknowledge that we did not discuss the issue of confidentiality when geocoding data using online services, and we appreciate the opportunity to briefly reflect on this topic.…”
Section: Dear Editormentioning
confidence: 99%